CredenceLedger: A Permissioned Blockchain for Verifiable Academic Credentials - Fernandez, Proceso L, Jr (Archīum Ateneo, 2018)
Blockchain, the underlying technology that powers cryptocurrencies such as Bitcoin and Ethereum, is gaining so much attention from different industry stakeholders, governments and research communities. Its application is extending beyond cryptocurrencies and has been exploited in different domains such as finance, E-commerce, Internet of Things (IoT), healthcare, and governance. Some key attributes of the technology are decentralization, immutability, security and transparency. This paper aims to describe how permissioned Blockchain can be applied to a specific educational use case - decentralized verification of academic credentials. The proposed Blockchain-based solution, named `CredenceLedger', is a system that stores compact data proofs of digital academic credentials in Blockchain ledger that are easily verifiable for education stakeholders and interested third party organizations.